Modeling the Risks of Blockchain Development in Improving the Resilience of the Medical Equipment Supply Chain - Atena Maleki; Masoumeh Zeinalnezhad; Tahereh Aliheydari Bioki; Ehsan Hedayati (مجله مدل سازی در مهندسی)
Blockchain technology is creating a huge revolution in all the world's industries and has become one of the most popular financial markets in the world. The field of medical equipment has not been deprived of the countless benefits of this technology and has started to use it, in addition to Providing the key objectives of the supply chain also brings transparency, traceability and resilience. In this research, taking into account the role of blockchain in the resilience of the supply chain of medical equipment, the risks of blockchain development in this field were evaluated and analyzed, and after analyzing the influence and dependence based on the interpretive structural equations procedure, the risks were identified. Hence, 10 main political and governmental risks, reliability, service, profitability, security, networking, organizational issues, privacy, social issues, environmental effects were identified and the risks were ranked based on fuzzy BWM and political and governmental risks They ranked first with a weight of 0.26, reliability ranked second with a weight of 0.15, and profitability ranked third with a weight of 0.127..